(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The essence of federalism should be searched for, not in the nuances of constitutional andlegal nomenclature, but in the economic, social, political, and cultural factors that have necessitated theexternal forms of federalism. The foundation of federalism is found in the community itself, not in itsinstitutional or constitutional framework. The federal characteristics of the society are expressed andsafeguarded by the federal government. In a federal system, there are two levels of government one at thecenter and one at the outside. It is the sacred duty of provincial governments to greater benefit from thelowest strata they reflect the desires and ambitions of the local populace. In contrast, the centralgovernment stands for national interests it is the mirror that reflects the state of the whole nation.National security and economic development are under the control of the federal government. This essayexamines the function of communist political parties in the federal government of India.